MODEL PERILAKU HUBUNGAN ANTARA KAWASAN HUTAN LINDUNG DAN KETERSEDIAAN AIR DI DAS CITARUM HULU (METODE ; SYSTEM DYNAMICS - Wibowo, Bobby
Wide of forest in Upper Citarum Watershed for year 1984 up to year 1996 have decreased 21,15%. While wide of forest in Upper Citarum Watershed for the year 1996 up to year 2002 have decreased 44%. The cause of forest degradation in Upper Citarum Watershed is estimated by forest change in Protected Forest Area become usage of other interests. Change of forest in Protected Forest Area is very bothering to water availibility in Upper Citarum Watershed, both of water in liquid form (rainfall, surface water and infiltration water) and also water in the form of gas (vapour). Trouble to water availability in Upper Citarum Watershed cause uncertainty to availability of regional water in the future. In order to depicting for the future behavior of relationship between forest change in Upper Citarum Watershed (as the cause system) and availability of its water (as the effect system), hence needed a model. System Dynamics method represent an effective method to develop a model in which it have relation between forest change and water availability in a Hydrological Cycle as a causality relationship which is not linear and represent closed system from the watershed so that can inform the simulation result of model in the form of behavior that happened of relation between forest change and water availability, and also the information by the model can depicting the future for the decision maker.The study used also Hydrological and Meteorological methods besides of System Dynamics method to equip analyzer utilize to calculating the level of Evapotranspiration, Surface Water Potency, Infiltration Water Potency and calculating Surface Runoff in Upper Citarum Watershed. The methods are ASCE Penman-Monteith 2000 method, Rational method dan Peter method. The simulation by System Dynamics method resulting that illegal Ioging is the primary cause of shattering forest and also the primary cause of forest change in Protected Forest Area at Upper Citarum Watershed. Another simulation by System Dynamics method and calculation using ASCE Penman-Monteith 2000 method, Rational method dan Peter method resulting that it have a significant relationship among degradationing of forest's wide, decreasing of Infiltration Water Volume, decreasing of Atmospheric Water Volume, increasing of Surface Water Volume, increasing of Surface Runoff and difference between maximum debit and minimum. Another simulation by System Dynamics method resulting that the collective agreement and awareness of stakeholders in Upper Citarum Watershed to protect of forest in Protected Forest Area wisely represent the basis for forest rehabilitation process into succeed so that wide of forest become recover. The other simulation by System Dynamics method and calculation using ASCE Penman-Monteith 2000 method, Rational method dan Peter method resulting that it have a significant relationship among recovelying of forest's wide, increasing of Infiltration Water Volume, increasing of Atmospheric Water Volume, decreasing of Surface Water Volume, decreasing of Surface Runoff and reduction of difference between maximum debit and minimum. In the real world many behavior of Stakeholders, realized or not, could affect to forest's wide degradation in Protected Forest Area at the watershed.Care and uncare habit of Stakeholders is the key to create the everlasting Protected Forest Area and to protect the availibility of its water at the watershed